Analisis Kandungan Nutrisi Nugget Ayam Terfortifikasi Daun Kelor (Moringa oleifera) - Aris, Muhammad; Asmaq, Nur (Journal of Pharmaceutical and Sciences, 2024)
The aim of this research was to observe the nutritional value enhancement of nugget products after fortification with moringa leaf powder. The research method employed was an experimental approach through a Completely Randomized Design (CRD) non-factorial with 4 treatments and 4 replications for each treatment. The treatments included in this study were without moringa leaf powder (A0), 5% moringa leaf powder (A1), 10% moringa leaf powder (A2), and 15% moringa leaf powder (A3). The parameters observed were the protein content, fat content, and water content of the nugget samples. The research results indicate that fortification with moringa leaves significantly increased the water content (by 53.63%) and protein content (by 13.21%), while significantly reducing the fat content (by 9.90%). This effect was observed across various concentrations, with the optimal concentration found in treatment A3.